2019
DOI: 10.3168/jds.2018-14581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant activities of bovine whey proteins before and after simulated gastrointestinal digestion

Abstract: Oxidative stress caused by free radicals has been implicated in several human disorders. Dietary antioxidants can help the body to counteract those reactive species and reduce oxidative stress. Antioxidant activity is one of the multiple health-promoting attributes assigned to bovine whey products. The present study investigated whether this activity was retained during upper gut transit using a static simulated in vitro gastrointestinal digestion (SGID) model. The capacity to scavenge free radicals and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 59 publications
9
35
0
Order By: Relevance
“…For example, tryptophan is a well-known antioxidant against peroxyl radicals and can exert its antioxidant ability by electron transfer mechanism or hydrogen atom transfer [39]. Phenylalanine with phenolic hydroxyl group has DPPH scavenging activity and ferric ion reducing power [40]. Balsaminoside C is a cucurbitane-type triterpenoid and can serve as an antioxidant agent for the treatment of reactive oxygen species-induced diseases [41].…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
“…For example, tryptophan is a well-known antioxidant against peroxyl radicals and can exert its antioxidant ability by electron transfer mechanism or hydrogen atom transfer [39]. Phenylalanine with phenolic hydroxyl group has DPPH scavenging activity and ferric ion reducing power [40]. Balsaminoside C is a cucurbitane-type triterpenoid and can serve as an antioxidant agent for the treatment of reactive oxygen species-induced diseases [41].…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
“…Endoproteases and exoproteases including bromelain, Neutrase, and Flavourzyme have been used to hydrolyze proteins to produce protein isolate hydrolysates showing antioxidant activities [ 16 ]. Among these proteases, bromelain (EC 3.4.22.32) is a cysteine endoprotease derived from pineapple stems, and it has also been demonstrated to be a safe and effective food supplement [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound assisted extraction has been considered as an efficient and green/ecofriendly technology to disrupt the matrices and subsequently release the target component by bubble cavitation at mild condition in short time [27, 28]. Meanwhile, it has been reported that the technique of enzymolysis could be employed to search the new and small molecular peptide with stronger DPPH• scavenging ability and other bioactivities [29, 30]. In addition, whether the stability of bioactivity was retained during the gastrointestinal digestive juice might be a large block for preparation of peptide with marked bioactivities practical application in human.…”
Section: Introductionmentioning
confidence: 99%